Histological analysis of the osseointegration of Ti-30Ta dental implants after surface treatment - Claro, Ana Paula Rosifini Alves [UNESP]; de Oliveira, João Augusto Guedes [UNESP]; Escada, Ana Lúcia do Amaral [UNESP]; Carvalho, Luciana Maria Ferreira [UNESP]; Louzada, Mário Jefferson Quirino [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP] (Springer Nature, 2013)
Metallic biomaterials are used to reinforce or to restore the form and function of hard tissues. Implants and prosthesis are used to replace shoulders, knees, hips and teeth. When these materials are inserted in bone several biological reactions happen. This process can be associated to surface properties (topography, roughness and surface energy). In this work, the influence of biomimetic surface treatment in the osseointegration of Ti-30Ta dental implants was evaluated. Ingots were obtained from titanium and tantalum by using an arc-melting furnace. They were submitted to heat treatment at 1,100°C for 1 h, cooled in water and cold worked by swaging. Then, screw-shaped implants (2.0 mm diameter by 2.5 mm length) were manufactured and they were implanted in a rat's femur. Animals were divided into two groups: untreated (control group) and treated (biomimetic surface treatment). They were sacrificed 30 days after implantation. For histological analysis, implants with surrounding tissue were removed and immersed in formaldehyde. Samples were embedded in polymethyl methacrylate and after polymerization, cut with a saw, polished and mounted on glass slides. The results obtained suggest that biomimetic surface treatment was able to promote an increase osseointegration on the surface of dental implants. © Springer-Verlag Berlin Heidelberg 2013.
Keywords: Dental implants; Histological analysis; Titanium alloys